Cadmium facilitates the formation of large lipid droplets via PLCβ2-DAG-DGKε-PA signal pathway in Leydig cells - Youjin Wang; Yuqing Liang; Zansheng Yuan; Wanwen Mai; Yang Leng; Runze Zhang; Jiayan Chen; Caiyong Lai; Hongxia Chen; Xiaoping Wu; Chao Sheng; Qihao Zhang (Ecotoxicology and Environmental Safety, 2023)
Cadmium (Cd) exposure damages the reproductive system. Lipid droplets (LDs) play an important role in steroid-producing cells to provide raw material for steroid hormone. We have found that the LDs of Leydig cells exposed to Cd are bigger than those of normal cells, but the effects on steroidogenesis and its underlying mechanism remains unclear. Using Isobaric tag for relative and absolute quantitation (iTARQ) proteomics, phosphodiesterase beta-2 (PLCβ2) was identified as the most significantly up-regulated protein in immature Leydig cells (ILCs) and adult Leydig cells (ALCs) derived from male rats exposed to maternal Cd. Consistent with high expression of PLCβ2, the size of LDs was increased in Leydig cells exposed to Cd, accompanied by reduction in cholesterol and progesterone (P4) levels. However, the high PLCβ2 did not result in high diacylglycerol (DAG) level, because Cd exposure up-regulated diacylglycerol kinases ε (DGKε) to promote the conversion from DAG to phosphatidic acid (PA). Exogenous PA, which was consistent with the intracellular PA concentration induced by Cd, facilitated the formation of large LDs in R2C cells, followed by reduced P4 level in the culture medium. When PLCβ2 expression was knocked down, the increased DGKε caused by Cd was reversed, and then the PA level was decreased to normal. As results, large LDs returned to normal size, and the level of total cholesterol was improved to restore steroidogenesis. The accumulation of PA regulated by PLCβ2-DAG-DGKε signal pathway is responsible for the formation of large LDs and insufficient steroid hormone synthesis in Leydig cells exposed to Cd. These data highlight that LD is an important target organelle for Cd-induced steroid hormone deficiency in males.